Recurrent left atrial myxoma in Carney complex: A case report of a familial pedigree. Issue 12 (March 2018) - Wang, Liaoyuan; Wang, Qing; Zhou, Yue; Xue, Qian; Sun, Xiao; Wang, Zhinong; Ji, Guangyu
Abstract: Rationale: Carney complex (CNC) accounts for up to two-thirds of familial cardiac myxoma, which is a rare autosomal dominant syndrome characterized by multiple mucocutaneous lesions and endocrine tumors. Mutation in the cAMP-dependent protein kinase A (PKA) regulatory (R) subunit 1 (PRKAR1A) gene has been identified as a cause of CNC. In this article, we report 3 first-degree relatives with cardiac myxoma who were diagnosed with CNC and underwent surgical resection. Presenting concerns: The recurrence of cardiac myxoma was detected in a 45-year-old male by echocardiography 5 years after the resection was carried out, without any additional symptoms. Family screening indicated that his brother and his brother's son also had a history of cardiac myxoma. Diagnosis: The echocardiography of the patient showed a 43 mm × 28 mm echo mass at the bottom of the atrial septum near anterior mitral leaflet. Sequencing of the patient's genomic DNA obtained from peripheral blood identified a p.E17X (c.491-492delTG) mutation in PRKAR1A, which encodes the type Iα regulatory subunit of protein kinase A. Interventions: The patient received redo cardiac myxoma resection and mitral valve repair under cardiopulmonary bypass. Echocardiographic surveillance was conducted after the surgery. Outcomes: The patient recovered quickly after the surgery and was discharged without any abnormality detected by echocardiography. Follow-up after 1 year showed no recurrence of the cardiac myxoma. Main lesson: We recommend echocardiographic surveillance of the affected individuals and their first-degree relatives at regular intervals, given the high risk of recurrence and the morbidity and mortality associated with cardiac tumors in any location.